CRALBP is a Highly Prevalent Autoantigen for Human Autoimmune Uveitis - Cornelia A. Deeg; Albert J. Raith; Barbara Amann; John W. Crabb; Stephan R. Thurau; Stefanie M. Hauck; Marius Ueffing; Gerhild Wildner; Manfred Stangassinger (Clinical and Developmental Immunology, 2007)
Cellular retinaldehyde binding protein (CRALBP) is an autoantigen in spontaneous equine recurrent uveitis. In order to test whether CRALBP contributes to human autoimmune uveitis, the specificity of antibodies from human uveitis patient's sera was first evaluated in two-dimensional (2D) Western blot analysis. Subsequent identification of the immunoreactive proteins by mass spectrometry resulted in the identification of CRALBP as a putative autoantigen. Additionally, sera from human uveitis and control patients were by Western blot using purified human recombinant CRALBP. Anti-CRALBP autoantibodies occur more frequently (P<.01) in human uveitis patients than in normal controls. Thirty out of 56 tested uveitis patient's sera contained autoantibodies reactive against CRALBP, compared to only four out of 23 normal control subjects. The presence of CRALBP autoantibodies in 54% of tested uveitis patients supports CRALBP as a possible autoantigen in human autoimmune uveitis.